Kinematics of women's sprint canoeing technique - Wainwright, B.; Low, C.; Mulloya, F.; Willmott, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Little is known about the biomechanics of sprint canoeing, especially for women's canoeing, and a quantitative kinematic description of the motion would help coaches to develop valid technique coaching models. Five highly-trained female canoeists were filmed at 150 Hz while undertaking a 50 s maximal effort on a canoe ergometer, whose trolley motions were taken to represent those of the boat. Selected boat, body and paddle kinematics were evaluated at three key stroke cyde events (Contact, Paddle Vertical, and End of Drive) and their patterns monitored across the stroke cycle. While no clear trends between the kinematics and power output emerged, a range of strategies were identified and the data represent an initial step in the construction of detailed technique models that can be used to evaluate and monitor individual athletes.